Mechanical and Structural Properties of Polyhydroxybutyrate as Additive in Blend Material in Additive Manufacturing for Medical Applications - Muhammad Zulhilmi Zainuddin; Ahmad Adnan Abu Bakar; Ahmad Nurhelmy Adam; ShahinoMah Abdullah; NizamTamchek; Muhammad Syafiq Alauddin; Mohd Muzamir Mahat; Nophadon Wiwatcharagoses; Ahmad Alforidi; Mohd Ifwat Mohd Ghazali (MDPI, 2024)
Indexed by WOS/Scopus/ERA